SS-31 protects diabetic nephropathy progression: A systematic review of in vivo and in vitro studies - Jonathan Christianto Sutadji; Dian Anggraini Permatasari Musalim; David Setyo Budi; Jennifer Susanto; Fanny Gunawan; Chaq El Chaq Zamzam Multazam; Citrawati Dyah Kencono Wungu (GarVal Editorial Ltda., 2024)
Context: Diabetic nephropathy is the leading cause of end-stage renal disease and also death in the world. Administration of Szeto-Schiller-31 (SS-31) as a potential therapeutic candidate that can decrease the renal function damage progressivity in diabetes needs to be comprehensively analyzed. Aims: To assess the protective effects of SS31 against the progressivity of diabetic nephropathy. Methods: This systematic review follows PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) guidelines 2020. Searches of databases (Pubmed, Science Direct, Scopus, ProQuest, and Springer) were done on 17 September 2023 in order to find articles related to the animal diabetic model and SS-31 treatment. Manual searches from medRxiv were also conducted to obtain additional evidence. Renal function, histopathology analysis, reactive oxygen species in vivo, and in vitro analysis were described. Results: There were six in vivo studies, each of which discussed the renal function, histopathology, and reactive oxygen species (ROS), and four in vitro studies that discussed ROS. The available data suggested that SS-31 improves kidney function by lowering urinary albumin excretion, proteinuria, serum creatinine, creatinine clearance, and BUN, supported by histopathological improvements. In addition, SS-31 also has the effect of lowering 8-hydroxy-2-deoxyguanosine (8-OHdG) level, malondialdehyde (MDA) level, and nicotinamide adenine dinucleotide phosphate (NADPH) expression. Conclusions: SS31 had a renoprotective effect that could prevent the worsening of renal function in diabetic mice. In addition, the results of histopathology and ROS analysis also support the positive results of SS-31 treatment. Further studies are required to confirm its findings.